Stability and activity of platinum nanoparticles in the oxygen electroreduction reaction: is size or uniformity of primary importance? - Paperzh, Kirill O.; Alekseenko, Anastasia A.; Volochaev, Vadim A.; Pankov, Ilya V.; Safronenko, Olga A.; Guterman, Vladimir E. (Beilstein Journal of Nanotechnology, 2021)
Platinum–carbon catalysts are widely used in the manufacturing of proton-exchange membrane fuel cells. Increasing Pt/C activity and stability is an urgent task and the optimization of their structure seems to be one of the possible solutions. In the present paper, Pt/C electrocatalysts containing small (2–2.6 nm) nanoparticles (NPs) of a similar size, uniformly distributed over the surface of a carbon support, were obtained by the original method of liquid-phase synthesis. A comparative study of the structural characteristics, catalytic activity in the oxygen electroreduction reaction (ORR), and durability of the synthesized catalysts, as well as their commercial analogs, was carried out. It was shown that the uniformity of the structural and morphological characteristics of Pt/C catalysts makes it possible to reduce the negative effect of the small size of NPs on their stability. As a result, the obtained catalysts were significantly superior to their commercial analogs regarding ORR activity, but not inferior to them in terms of stability.
Keywords: durability; electrocatalysts; morphology control; oxygen reduction reaction; platinum nanoparticles; size distribution; spatial distribution